Influenza as a Cause of SIADH Related Hyponatremia: A Case Report - Gaglani, Bhavita (J Clin Diagn Res, 2017)
Syndrome of Inappropriate Secretion of Antidiuretic Hormone (SIADH) is one of the most common causes of hyponatremia in hospitalized patients. The distinct aetiologies and co-morbidities associated with hyponatremia pose substantial challenges in identifying and managing this disorder. Several infectious causes of SIADH are reported but hyponatremia associated with SIADH and influenza virus infection is less commonly seen. We present a case of hyponatremia associated with influenza, which was subsequently diagnosed as SIADH.